Effect of water on the interfacial structures of room‐temperature ionic liquids. (2nd September 2018) - Kawada, Shouhei; Kodama, Eri; Sato, Keisuke; Ogawa, Shuhei; Watanabe, Masaya; Okubo, Hikaru; Sasaki, Shinya
Abstract : The interfacial structures of cyano‐based room‐temperature ionic liquids play a very important role in reducing friction. However, the presence of water impairs their tribological performance. The interfacial structures and friction forces of 1‐ethyl‐3‐methylimidazolium dicyanamide, [EMIM][DCN], and the effect of water on these structures and forces were investigated using atomic force microscopy. In addition, the interaction of water and [EMIM][DCN] was evaluated using Fourier‐transform infrared (FT‐IR) spectroscopy. Multiple repulsive layers were observed in the [EMIM][DCN] solution. This solution showed low friction force because these repulsive layers worked as protective layers against friction. On the other hand, the specific repulsive layer characteristics of [EMIM][DCN] could not be observed in a [EMIM][DCN] + 2 wt% H2 O solution. FT‐IR results indicated that the layer structure of [EMIM][DCN] was disturbed by the addition of H2 O. Therefore, the solution containing water exhibited a high friction force.